Meander '94. (Apatin : Galerija Meander, 1994)
Bogdanovic, Kosta ; Jevric, Olga ; Jelenkovic, Dragan ; Krojic, Slobodan ; Krnajski, Dragoslav ; Marinkov, Mladen
Meander '94, Galerija Meander, Apatin, jun 1994
boek